A köztársasági elnöki kegyelem a büntetőjog szempontjából - Hadházi, Dávid (Debreceni Jogi Műhely, 2015)
The individual pardon, exercised by the President of the Republic, has recently become the centre of attention in the media and among the lawyers in context of life imprisonment without parole eligibility. This prompts me to investigate the presidential pardon in this article. I am dealing with the origins and the standardization of pardon, then I move on to the conditions and criteria the Head of State can take into consideration when making the decision. Afterwards, I am presenting some statistics. The power of pardon is stipulated by the Fundamental Law of Hungary, and the specific rules can be found in the Criminal Code, the Criminal Procedure Act and the Punishment Executive Act. I am focusing on the last one, in which the Government and the Parliament have redressed the problems of life sentence, regarding human rights, with a compulsory procedure of pardon, thus giving the convict the hope of being released from prison. However, this solution raises a few questions, so arguments can be made both for and against it.